Throughput analysis of PD-CSMA/CA in two interference-limited cells - Lau, Chiew Tong (2013)
The Payload Dropping CSMA/CA is a cross-layer modified version of the CSMA/CA protocol that can serve as an alternative to the carrier-sense threshold approach for improving throughput in multi-cell networks when the number of co-channel, interference-limited cells is small. The basic idea behind it is a qualification of each signal during the entire preamble and header stages of its reception, and then aborting the payload if the signal is deemed to be from a source outside the cell not strong enough to interfere with signals transmitted within the cell. Using a two-cell scenario, we formulate its upper throughput bound using a Markov chain model, and subsequently assess the formulations with simulation results.